The Effect Of Quantum Teaching Learning Model On The Quality Of Kmi Class 1 Al-Quran Reading Students (Experimental Research At Riyadlul Ulum Islamic Boarding School Wadda’wah Condong) - Miftahul Ulum; Ilham Ramadhan (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2018)
Riyadlul Ulum Islamic Boarding School Wadda’wah Condong was one of the Islamic educational institutions that focused on Qur'anic learning. This institution strives to increase the students’ ability to read the Qur'an's students by teaching the Qur'an. Therefore, the instructors have applied special learning models in the teaching and learning process. For this reason, the researchers tried to analyze whether there was an influence on the Quantum Teaching learning model that was used towards the quality of the reading of the Qur'anic students. This research used experimental research (true experiment design) in which the hypothesis in this study was the application of Quantum Teaching learning models. Furthermore, it also analyzed the appropriate methods that significantly influence the students’ ability of in Riyadlul Ulum Wadda'wah Islamic Boarding School in reaching good reading al -Qur'an (tartil). In collecting data, researchers used the test method, and documentation. Moreover, to analyze the data collection, researchers used an independent formula sample t-test. The most important result of this study was the implementation or application of the Quantum Teaching learning model has a significant influence on the quality of students' Qur’an reading after the trial process. This was proven by a significant increase in the value of the difference between the control class 79, 7 and experimental value 87.76. Therefore, the Quantum Teaching learning model was able to facilitate the teachers in teaching students and to help the students to achieve the goal of teaching al-quran.